Common pediatric medical procedures. Giving immunizations - Kelleher, Kelly J.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2014)
A complete review and demonstration of the procedure for giving immunizations, including complete demonstrations of the techniques for giving intramuscular and subcutaneous injections.
Presenter: Kelly J. Kelleher.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 15, 2020)
Keywords: Immunization of children; Vaccination of children; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films